Clinical simulation training for the adequate management of obstetrics emergencies: A narrative review - Najat Boucetta; Mustafa El Alaoui (Medwave, 2023)
Obstetric emergencies are critical situations that jeopardize the health of both the mother and the baby during pregnancy or childbirth. This study aimed to validate the effectiveness of clinical simulation training in managing these situations. We conducted a narrative review of studies published between 2008 and 2022, collected from databases including Scopus, Sciencedirect, PubMed, Springer, Scielo, and Google Scholar. Data from studies that met our inclusion criteria were meticulously gathered and summarized. Our findings strongly emphasize that clinical simulation emerges as a highly effective tool in the training of healthcare professionals. This training translates into substantial improvements in various aspects, including performance, knowledge, confidence, satisfaction, attitudes, self-efficacy, teamwork abilities, and the skills necessary to confront critical obstetric situations such as postpartum hemorrhage, eclampsia, shoulder dystocia, maternal cardiac arrest, umbilical cord prolapse, and cesarean sections. Importantly, this training reduces the inherent risks associated with learning on real patients and aligns with the highest ethical standards. Additionally, our results underscore that interdisciplinary collaboration in the management of obstetric emergencies proves to be an effective strategy for providing comprehensive patient care. However, it is crucial to highlight that, in order to ensure patient safety and promote a teamwork approach, it is imperative for healthcare professionals to receive adequate training and be duly qualified. Although we acknowledge that implementing clinical simulation training can entail significant costs and require substantial resources, we firmly believe that this strategy continues to hold immeasurable value in the education of professionals in this field. Ultimately, we anticipate that future high-quality research will further fortify the evidence base regarding best practices in clinical simulation training for obstetric emergencies, thus contributing to enhanced patient outcomes and the overall quality of healthcare in this critical domain.